Impact of Clinical Pharmacist Interventions on Economic Outcomes in a Cardiology Setting in Qatar - Daoud Al-Badriyeh (832403) (2023)
We sought to investigate the economic impact of preventing adverse events in a cardiology setting in Qatar as an effect of the clinical pharmacist as an intervention. This is a retrospective study of interventions by clinical pharmacists within an adult cardiology setting in a public healthcare setting (i.e Hamad Medical Corporation). The study included interventions that took place in March 2018, July 15, 2018 to August 15, 2018, and January 2019. The economic impact was measured via calculating the total benefit, defined as the sum of the cost savings and the cost avoidance. Sensitivity analyses were adopted to confirm the robustness of the results. The pharmacist intervened in 262 patients, resulting in 845 interventions, with appropriate therapy (58.6%) and dosing/administration (30.2%) being the most frequent categories of reported interventions. Cost savings and cost avoidance resulted in QAR-11,536 (USD-3169) and QAR1,607,484 (USD 441,616), respectively, yielding a total benefit of QAR1,595,948 (USD 438,447) per 3 months and QAR6,383,792 (USD 1,753,789) per a year. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2023.101838